Conflating Capacity & Authority: Why We're Asking the Wrong Question in the Adolescent Decision-Making Debate - Salter, Erica K. (The Hastings Center report, 2017)
Whether adolescents should be allowed to make their own medical decisions has been a topic of discussion in bioethics for at least two decades now. Are adolescents sufficiently capacitated to make their own medical decisions? Is the mature-minor doctrine, an uncommon legal exception to the rule of parental decision-making authority, something we should expand or eliminate? Bioethicists have dealt with the curious liminality of adolescents—their being neither children nor adults—in a variety of ways. However, recently there has been a trend to rely heavily, and often exclusively, on emerging neuroscientific and psychological data to answer these questions. Using data from magnetic resonance imaging and functional MRI studies on the adolescent brain, authors have argued both that the adolescent brain isn't sufficiently mature to broadly confer capacity on this population and that the adolescent brain is sufficiently mature to assume adolescent capacity. Scholars then accept these data as sufficient for concluding that adolescents should or should not have decision-making authority. Two critical mistakes are being made here. The first is the expectation that neuroscience or psychology is or will be able to answer all our questions about capacity. The second, and more concerning, mistake is the conflation of decision-making capacity with decision-making authority.